Impacts of grazing management strategies on forage canopy structure in multi-species pastures during the wet-dry transition period - L. F. Penteado; A. C. L. Batista; A. F. B. Ongaro; M. M. Vieira; F. F. Simili; R. L. D. Costa; C. M. P. Barbosa; S. D. Simão; F. M. A. Gimenes (Boletim de Indústria Animal)
The condition of pastures during the wet-dry transition period reduces livestock production since there is an increase in dead material and a reduction in green tissues. This study evaluated the influence of grazing management strategies on the structure of the forage canopy during the wet-dry transition period. The pastures were composed of Aruana guineagrass (Megathyrsus maximum Syn. Panicum maximum cv. Aruana) and three legumes: Macrotyloma (Macrotyloma axillare), Calopo (Calopogoinum mucunoides), and Stylo (Stylosanthes macrocephala + Stylosanthes capitata). The treatments corresponded to four forage canopy heights (15, 30, 45, and 60 cm), and the grazing management strategies involved steady or variable stocking rates with sheep. The experiment was conducted in a randomized complete block design with four replications totaling 16 experimental units (paddocks). The masses of grass leaf blades and stems were higher at heights of 45 and 60 cm (P = 0.002), while the proportion of dead material was smaller in these than in the short pastures (15 and 30 cm) (P = 0.0497). There was an increase in the proportion of dead material over the dry-water transition period. The presence of grass and legume leaves was higher in the upper stratum of tall pastures (45 and 60 cm) and the proportion of legumes did not differ between grazing management strategies (P > 0.05). These strategies were represented by canopy heights of 45 to 60 cm and showed more leaf mass, less dead material, and better pasture structure, so these parameters can be used during the wet-dry transition period.